Effectiveness of hard court slide braking technique and influencing factors in elite college tennis players - Ji, Y.; Gao, T.; Zhang, W.; Zhang, R.; Wang, Y.; Xu, L.; Wang, X.; Wen, X. (Journal of Exercise Science & Fitness, 2025)
Objective The study aimed to evaluate the effectiveness of hard court slide braking technique of elite college tennis players and to analyze the factors that influence the use of hard court slide braking technique.